The Renin-Angiotensin-Aldosterone System in Vascular Inflammation and Remodeling - Maricica Pacurari; Ramzi Kafoury; Paul B. Tchounwou; Kenneth Ndebele (International Journal of Inflammation)
The RAAS through its physiological effectors plays a key role in promoting and maintaining inflammation. Inflammation is an important mechanism in the development and progression of CVD such as hypertension and atherosclerosis. In addition to its main role in regulating blood pressure and its role in hypertension, RAAS has proinflammatory and profibrotic effects at cellular and molecular levels. Blocking RAAS provides beneficial effects for the treatment of cardiovascular and renal diseases. Evidence shows that inhibition of RAAS positively influences vascular remodeling thus improving CVD outcomes. The beneficial vascular effects of RAAS inhibition are likely due to decreasing vascular inflammation, oxidative stress, endothelial dysfunction, and positive effects on regeneration of endothelial progenitor cells. Inflammatory factors such as ICAM-1, VCAM-1, TNFα, IL-6, and CRP have key roles in mediating vascular inflammation and blocking RAAS negatively modulates the levels of these inflammatory molecules. Some of these inflammatory markers are clinically associated with CVD events. More studies are required to establish long-term effects of RAAS inhibition on vascular inflammation, vascular cells regeneration, and CVD clinical outcomes. This review presents important information on RAAS’s role on vascular inflammation, vascular cells responses to RAAS, and inhibition of RAAS signaling in the context of vascular inflammation, vascular remodeling, and vascular inflammation-associated CVD. Nevertheless, the review also equates the need to rethink and rediscover new RAAS inhibitors.